Correlation of Alpha-Fetoprotein Levels with ThreePhase Contrast CT-Scan Finding in Hepatocellular Carcinoma Patients at Dr. Mohammad Hoesin General Hospital Palembangin 2022 – 2023 - Florence Tania Nainggolan; Imam Suprianto; Legiran . (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Background: Hepatocellular carcinoma (HCC) is the primary liver tumor, accounting for 90% of liver tumor cases. Currently, laboratory tests are needed to monitor tumor progression, predict prognosis, and determine appropriate therapy without radiological examinations, one of which is Alpha-Fetoprotein (AFP). This study aims to determine the correlation between AFP levels and three-phase contrast CT-Scan findings in HCC patients at Dr. Mohammad Hoesin General Hospital Palembang.